Design of capacitive measuring system for high frequency transducer band - Nurul Arfah binti Che Mustapha (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Capacitance measurement system is no longer a fringe technology that only can be used in the factory to select a defect product on the assembly line. It is a mature technology employed in thousand of products and a newer application, coming into widespread use is in the consumer product of human-to-machine interfaces such as on the mobile phone, PC peripherals, portable digital entertainment devices, appliances, remote controls, access control and digital cameras application. It is also reported that this technique has been used in industrial applications for many years to measure liquid levels, humidity, and material composition. The proposed capacitance-tovoltage converter is designed based on CMOS 0.13 μm technology using switchedcapacitor technique which reduces size of the circuit and lowers the power supply requirement. The circuit is able to detect a capacitance, Cx change within a wide range of capacitance variation under two detectable range; first is lower detectable range in femto Farad from 100 fF to 1640 fF and secondly in pico Farad detactable range from 120 pF to 380 pF. The output voltage of the circuit varies linearly with the variation of capacitive transducer within these detectable ranges. The output voltage for both the detectable range of capacitance Cx shows less than 1 V with power dissipation of 0.939 mW. The evaluation of the proposed circuit is done by analytical approach and using the simulation tool of PC based Simulation Program for Integrated Circuit Emphasis (PSpice) OrCAD version 16.0. The circuit requires less supply voltage, able to detect wide capacitive sensors capacitance variation, suitable to be used at high frequency and produces less power consumption. The proposed capacitance-to-voltage converter can be used in various capacitive sensors such in communication, automotive and medical field that are making use of high frequency system.